Maternal Socio-Demographic Factors and Mother-to-Child Transmission of HIV in the North Region of Cameroon - Celine Nguefeu Nkenfou; Marie-Nicole Ngoufack; Georges Nguefack-Tsague; Barbara Atogho; Constantin Tchakounte; Brian Bongwong; Carine Nguefeu-Tchinda; Elise Elong; Laeticia-Grace Yatchou; Joel Kameni; Aline Tiga; Wilfred F Mbacham; et al. (International Journal of Maternal and Child Health and AIDS, 2023)
Background and Objective: Socio-demographic factors are important risk factors for HIV infection. Maternal socio-demographic factors associated with HIV transmission from mother to child are not well elucidated to our knowledge. This study aimed to assess the maternal socio-demographic factors associated with HIV vertical transmission.